Economic Evaluation Analysis of PEGylated Poly(amidoamine) Dendrimer Production by Divergent Synthesis Method - Veronica, Jessica; Nandiyanto, Asep Bayu Dani (Research and Social Study Institute, 2023)
The purpose of this study is to evaluate the viability of a large-scale divergent growth synthesis PEGylated dendrimer poly(amidoamine) (PAMAM) production project. Engineering and economic evaluations were used to determine the results of this feasibility study. Engineering evaluation is based on a review of the initial plant design and stoichiometry calculations. While a number of factors, including the payback period, gross profit margin, cumulative net present value, etc., are used to evaluate the economic evaluation. The results of this analysis confirm that PEGylated PAMAM dendrimer may be produced on an industrial scale. In this project, 250 grams of PEGylated PAMAM dendrimer was obtained per cycle and the total profit earned was USD 4,656,187,677.16 in 20 years. Payback Period analysis shows that the investment will be profitable after more than two years. To ensure project feasibility, projects are estimated from ideal to worst conditions in production, including salaries, sales, raw materials, utilities, and external conditions such as taxes.